The brothers Grimm - Michaelis-Jena, Ruth, author. (New York)
1 online resource
Keywords: This is the first modern biography of the Brothers Grimm, first published in 1970. It is a study of them in their background of late eighteenth-century and nineteenth-century Germany, and shows the position they held in their society as founders of Germanic philology, as members of the 'Gttingen Seven', and inside the circle of the German Romantics. Jacob and Wilhelm Grimm were pioneers in the recording of authentic traditional stories. Gradual revisions gave these tales the form in which they have come down to us. Even if more recently the custom has been to leave stories as they were told, the astonishing currency of the Grimms' collection is due largely to the brothers' editorial work. The Grimms' lasting fame, as Michaelis-Jena points out, may well rest on the fact that by their insistence on 'genuine and true recording' they turned the amateur antiquarian into the professional folklorist. Ruth Michaelis-Jena has worked for many years on the Brothers Grimm, and has had access to little known material at various libraries and museums in Germany.